The rotation of low mass stars at 30 Myr in the cluster NGC 3766. Issue Volume 15:Issue S354(2019) (June 2019) - Roquette, Julia; Bouvier, Jerome; Moraux, Estelle; Bouy, Herve; Irwin, Jonathan; Aigrain, Suzanne; Lachaume, Régis
Abstract: Together with the stellar rotation, the spotted surfaces of low-mass magnetically active stars produce modulations in their brightness. These modulations can be resolved by photometric variability surveys, allowing direct measurements of stellar spin rates. In this proceedings, we present results of a multisite photometric survey dedicated to the measurement of spin rates in the 30 Myr cluster NGC 3766. Inside the framework of the Monitor Project, the cluster was monitored during 2014 in the i-band by the Wide Field Imager at the MPG/ESO 2.2-m telescope. Data from Gaia-DR2 and grizY photometry from DECam/CTIO were used to identify cluster members. We present spin rates measured for ⁓200 cluster members.